Breaking the Chains of Violence: Celie’s Journey in Spielberg’s The Color Purple - Christian Wongso Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
The African American films influence social perceptions, cultural values, and representation in media and how they reflect contemporary issues such as politics, gender, and race. Steven Spielberg decided to take on the challenge of directing The Color Purple (1985) because he was inspired by the highly influential novel by Alice Walker. This thesis intends to reveal the violence and resistance experienced by Celie as an American African woman in The Color Purple. Using Johan Galtung's theories of violence I can identify types of violence that Celie experiences which are physical, psychological, and cultural. I also apply Patricia Hills’ theory on empowerment to analyze the way Cellie frees herself from the violence by creating a positive image of herself, and by getting support from the other black women. In conclusion, The Color Purple provides an in-depth analysis of how a woman overcomes a patriarchal form of violence and achieves personal autonomy.